Bibliometric Analysis: Application of Blended Learning in the Development of Digital Skills in the Era of Digital Education - Fricelia Budita Ayu; Eko Risdianto (CV Media Inti Teknologi, 2023)
In the current era characterized by rapid and widespread technological progress, digital skills have become an important factor in shaping individual success and societal progress. Digital skills cover a wide range of proficiencies, including digital literacy, programming, data analysis, online collaboration, and information security. In the world of education, a lot of research has been carried out on digital skills, one of the most research topics is the application of blended learning to improve digital skills. Therefore, researchers conducted a bibliometric analysis of the application of blended learning in developing digital skills in the era of digital education which aims to conduct a comprehensive exploration of existing literature. This research involved a comprehensive approach combining a systematic literature review and bibliometric analysis to explore the development of digital skills through online learning and assess its impact. Additionally, the use of VOSviewer software to visualize bibliometric networks is also discussed. The research results show that six different thematic clusters were found in the literature on digital skills development in the digital education era. Each cluster summarizes a set of recurring keywords that describe existing research trends, providing valuable insight into the landscape of the field. It can be concluded that this research contributes to the growing understanding of digital skills development through online learning and highlights its transformative potential in the world of education.